+0  
 
0
30
1
avatar

Can someone solve this please?

 
 Jun 3, 2021
 #1
avatar+119785 
+1

3^(2x - 1)  =   36  * 2 (1 - 2x)

 

Note  that we  can  write     2 ^(1-2x)   =  [ 2^(-1) ] ^(2x - 1)  =    1 /  [ 2^(2x - 1)]

 

So   we  have  that

 

3^(2x - 1)  =  36  /  [ 2^(2x - 1)]         multiply  both sides by  2^(2x - 1)

 

3^(2x - 1)  *  2^(2x - 1)   =   36

 

3^(2x)/3  *  2^(2x)  / 2  =    36

 

9^x   * 4^x  /   6     =  36          multiply both sides  by  6

 

9^x  * 4^x   =   216

 

(9 * 4)^x   =  216

 

36^x   =  216

 

(6^2)^x   =  6^3

 

6^(2x)  = 6^3           equate  exponents

 

2x  =  3

 

x   = 3/2

 

 

cool cool cool

 Jun 3, 2021

44 Online Users

avatar
avatar
avatar
avatar